Crisis and Homesickness: A New Opportunity for Brain Gain in Latin America? - Pacheco Iván F. (International Higher Education, 2015)
While some industrialized countries face a surplus of PhDs in many fields of knowledge, developing countries face the opposite problem. This might be a great opportunity for Latin American countries to attract talent. However, most countries do not have a clear policy for the recruitment of faculty abroad and, when they do, it is mostly focused on recovering their own expatriates from their work abroad.